Corporate financial management - Emery, Douglas R.; Finnerty, John D. (London : Prentice-Hall International, 1997)
This work integrates the major development made in finance since the mid-1970s, such as principal-agent considerations, asymmetric information considerations, and contingent claims analysis.
Card: Calculator guide for financial management.
Includes bibliographical references and index.
Keywords: Corporations -- Finance; Corporations -- Finance -- Management